El derecho constitucional de petición en la Legislación ecuatoriana - García Falconi, José (2024)
It should be notad that the human being is above all car rylng a sertes of ríghts which at all times can enforce it to power. Of the 444 articles that have the Constitulion of the Republic, 74 refer to rights, especially found in Arts. 12 to 82, but we also have duties and responsibilities are outlined in Art. 83. We underline that fundamental rights are the most direct expression of human dignity , or human beings have fundamental rights have dignity or quality human person , and between these fundamental ríghts , we have the request , whlch must be respectad and ensured in the historie moment we are living our country, because only in this way we will be building the constitutional State ot rights and justice , social, that says Art. 1 of the Conslitution of the Re public.